Balanced Scorecard as a Performance Measurement Tool for PT Aneka Tambang Tbk Listed on the Indonesia Stock Exchange - Oktavia Sari, Fhara; Sugianto, Sugianto; Yusnita Yamin, Nina; Ilham Pakawaru, Muhammad (Lafadz Jaya Publisher, 2025)
This research aims to assess the performance of PT. Antam Tbk uses the Balanced Scorecard as a performance measurement tool for 2021-2023. The company's performance measurement will utilize four perspectives from the Balanced Scorecard, namely the financial perspective, the customer perspective, the internal business process perspective, and the learning and growth perspective. This study adopts a descriptive design and relies on secondary data, including annual reports and financial statements of PT. Antam Tbk for 2021-2023. The results show that the company's financial perspective shows a strong ability to generate profits. However, there was a significant decline in performance in 2023. Both the customer perspective and the internal business process perspective show similar results, experiencing a considerable decline every year. Regarding the perspective of learning and growth, it can be concluded that PT. Antam Tbk showed inconsistent performance in human resource development, which was reflected in fluctuations in employee productivity.